THE SYNTHESIS OF METALLOCENE CALIX[4]ARENES - Beer, P; Keefe, A (Kluwer Academic Publishers, 1987)
The condensation of 1,1′-bis(chlorocarbonyl)metallocenes and p-tert-butylcalix[4]arene in toluene leads to novel metallocene calix[4]arenes in which the metallocene subunit bridges the opposite hydroxy groups of the parent calixarene. © 1987 D. Reidel Publishing Company.